2019
DOI: 10.35829/econbank.v1i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Indikator Makro Dan Harga Emas Dunia Terhadap Indeks Harga Saham Syariah (Jakarta Islamic Index)

Abstract: This study aims to determine macroeconomic factors such as interest rates, inflation, exchange rates, gross domestic product, and world gold prices in the Jakarta Islamic Index. This study uses time series data for 2015-2017. The data analysis technique used in this study is Multiple Linear Regression. The results of the study show that interest rates and exchange rates have negative effect on the Jakarta Islamic Index. While the world gold price looks positiveeffect towards the Jakarta Islamic Index. Meanwhil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 0 publications
0
12
1
2
Order By: Relevance
“…Gold has a significant negative effect on JII, which means that a one percent increase in gold can cause a decrease in JII by as much as 5.03 percent. The results are not in accordance with Utoyo & Riduwan [13], Agestiani & Sutanto [14] where gold has a positive effect. However, according to Setiawan's research [15], gold has a negative, insignificant effect.…”
Section: Vector Error Corrction Model (Vecm)contrasting
confidence: 70%
See 1 more Smart Citation
“…Gold has a significant negative effect on JII, which means that a one percent increase in gold can cause a decrease in JII by as much as 5.03 percent. The results are not in accordance with Utoyo & Riduwan [13], Agestiani & Sutanto [14] where gold has a positive effect. However, according to Setiawan's research [15], gold has a negative, insignificant effect.…”
Section: Vector Error Corrction Model (Vecm)contrasting
confidence: 70%
“…Utoyo & Riduwan [13], Agestiani & Sutanto [14], found that the gold price on the Jakarta Islamic Index (JII) has a positive effect. However, Setiawan [15], partially, the World Gold Price Variable has no significant effect on JII.…”
Section: Introductionmentioning
confidence: 99%
“…Dengan kata lain JII menjadi panduan bagi investor yang takut dana investasinya tercampur dengan dana ribawi. Kemudian JII juga menjadi patokan kinerja (Benchmark) dalam memilih portofolio saham investasi syariah [19]. JII merupakan salah satu tolak ukur untuk mengukur kinerja investasi syariah di saham.…”
Section: Pendahuluanunclassified
“…Significant effect on the Indonesian Sharia Stock Index (ISSI). Furthermore, research according to Agestiani and Sutanto (2019) found that world gold prices positively affected the Jakarta Islamic Index (JII).…”
Section: Introductionmentioning
confidence: 99%